Building competitive regions strategies and governance. (OECD, 2005)
In recent years, the main focus of territorial policy has been on sustaining growth, not only to address relative decline, but also to make regions more competitive. Putting this in practice is complicated because different regions have different characteristics (urban, intermediate, industrial, rural, etc.), which imply specific policy and investment needs. This report assesses the strategies pursued by OECD member governments to address the competitiveness of regional economies and the accompanying governance mechanisms on which the implementation of these strategies rests. The report is principally based on findings from the series of reviews undertaken by the OECD Territorial Development Policy Committee at national and regional levels.--Publisher's description.